The Influence of Digital Culture and E-Leadership on Operational Performance through Digital Capability: A Study on Study Programs at XYZ University - Jamil, Dina Nur Maulidiah; Pasaribu, Rina Djunita (The Eastasouth Management and Business, 2025)
The aim of this study is to examine the effect of e-leadership and digital culture on operational performance through digital capability in study programs at XYZ University. Utilizing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), 120 respondents who are heads of study programs, quality assurance coordinators, and administrative officers were targeted to collect data. The findings indicate that digital culture and e-leadership both directly impact operational performance, as well as digital capability. Digital capability also has a direct impact on operational performance. Digital capability partially mediates the relationship between digital culture and operational performance but does not significantly mediate the influence of e-leadership. Among all the measures, e-leadership has the strongest influence on operational performance. This study places the strategic role of leadership and digital values at the forefront as drivers of institutional performance, and illustrates that the transforming capability dimension of digital capability is underdeveloped. Practical and theoretical implications for maximum digital transformation by higher education institutions through synergistic cultural and leadership approaches are presented by these results.